THE EVOLUTION OF DISTANCE LEARNING IN EDUCATION: ENTERING THE DIGITAL ENVIRONMENT - Tamuli, Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores the evolution of distance learning (DL), tracing its development from correspondence courses to technologically advanced, interactive digital environments. It examines how DL has transformed from a passive content delivery system into an enriched educational model fostering autonomy, engagement, and student-centered learning. Through a synthesis of past and current research, the study highlights shifting perceptions among students and faculty, noting that while instructors often express skepticism about the quality of DL compared to traditional learning (TL), students increasingly report high satisfaction, greater motivation, and improved performance in online environments. Special attention is given to the demographic profile of distance learners, who are often adult, non-traditional students balancing multiple life responsibilities. The study incorporates educational theories such as Hackman and Oldham’s Job Characteristics Model and Moore’s Transactional Distance Theory to contextualize findings on learner engagement, motivation, and feedback mechanisms. It further identifies a gap in student-faculty perceptions regarding technology integration and underscores the potential of hybrid learning models to bridge these gaps, particularly for traditional undergraduate students. Empirical findings indicate that DL fosters higher task significance, autonomy, and immediacy of feedback, contributing to greater learner ownership. However, challenges remain in delivering technical or abstract content and ensuring real-time instructional adaptability. The research concludes with a call for broader implementation of hybrid instructional models that combine the flexibility of DL with the interpersonal benefits of face-to-face learning. Limitations such as sample scope, reliance on self-reporting, and narrow disciplinary focus are acknowledged, with recommendations for future studies to include diverse learner populations and cross-disciplinary perspectives.